Heterogeneity and perception congruence in retail projects in UAE - Airan, Hebah Mohammad Kamel (2016)
The main purpose of this study is to scrutinize on whether the various demographic differences contained within a project management teams affects the decision making of the retail projects in terms of the failures or the success in the UAE. The objectives of the study have been achieved through use of the quantitative research design. A study on the theoretical framework has also been used in bringing on board the advent of wider scope of study topic with keen attention to the heterogeneity that is depicted in project management team in retail projects in UAE. The research findings indeed confirm that there is congruence in project management homogeneity and the advent of demographic difference of the workforce. The high level of globalization and dynamism in the project management make it difficult to assess the actual impact of cultural practices on project management in UAE, Also, work experience as factor for project management emerged as a limitation. The conjectural framework of the research conducted is to provide functional individuals who will grow with proper skills and become intellectuals. The same people with this knowledge will come to be future managers and good role model to the society. Their managerial expertise will help in achieving the goals of any organization by combining efforts with other influential people hence boosting the global economy. The research airs out issues like age, gender, and culture and work experience influencing project related decisions in an organization hence providing an adequate benchmark study, This provides a good ground for more research executions so as to come up with better solutions on how to conduct and revise projects about more demographic differences.